Strategi Implementasi Kebijakan Pengembangan Kawasan Pariwisata Pasar Rebo Purnawarman Situ Buleud di Kabupaten Purwakarta - Cika Siskawati; Sutarto Mochtar; Edah Jubaedah (Jurnal Media Administrasi Terapan, 2022)
Research on policy strategies for the development of the Rebo Purnawarman Situ Buleud Market area is motivated by the problem of the lack of involvement of various parties, the availability of resources, the lack of public awareness, traders' complaints, and the attitude of the government. This study uses analysis with the Van Meter Van Horn model to analyze policies and SWOT analysis in analyzing the development strategy of the Rebo Purnawarman Situ Buleud Market Area. The results of the study conclude that the implementation based on the Van Meter Van Horn model analysis is known to be running in accordance with the policies contained in the Regional Regulations and Missions of Purwakarta Regency contained in the Purwakarta RPJMD, but has not run optimally. The SWOT strategy concludes that the policy strategy that must be taken is to fix the tourism sector in order to increase economic growth, guarantee security and peace from the Purwakarta Regional Government, promote tourism in increasing economic activity, improve planning and management systems, optimize area management, increase human resources in the tourism sector, strengthen coordination Area management, coordinating street vendors, increasing public awareness, aligning policies, and managing traders.